Women in a situation of homelessness and violence: a single-case study using the photo-elicitation technique - Clara Isabel Posada-Abadía; Carolina Marín-Martín; Cristina Oter-Quintana; María Teresa González-Gil (BMC, 2021)
Abstract Background Violence against women places them in a vulnerable position with regard to homelessness. Although sometimes invisible, women's homelessness is a complex reality shrouded in dramatic biographies that should be sensitively addressed to avoid revictimization. Methods With the aim of understanding the chaotic discourse of homeless women's experiences of violence, a qualitative single-case study was conducted using the photo-elicitation technique. Data were analyzed in accordance with grounded theory. Results The participant's discourse could be summarized in the following categories: "Living in a spiral of violence", "Confronting vulnerability and violence", "Being a strong woman", "New family networks", "Re-building mother-child relationships", and "Nurturing spiritual wellbeing". Conclusions Supporting homelessness women requires an approach that focuses on the prevention of re-victimization and the consequences of violence in terms of physical and mental health. Shelters are spaces of care for recovery and represent referential elements for the re-construction of self.